EKSPLORASI KONSEP BARISAN DENGAN METODE PEMBELAJARAN BERBASIS KOMPUTER - Kusumaningsih, Anjani
Nowadays, the use of computer simulation in learning process has signicantly in- creased rapidly. The use of this technology is so called CBL (Computer Based Learning). The aim is to visualize many basic concepts in mathematics, in order to help students to understand those concepts. In this project, we will examine one of the topics of mathematics learning at secondary school. That is the basic concepts of the sequence theory. The study is focused on the Fibonacci sequence and the sequences derived from the dierence equations. We then explore the sequences for the geometric and analytic aspects. Furthermore, we work out a simple simulation computer program to visualize the concept of the sequences.